Knowledge, attitude and practice of hand hygiene among healthcare workers caring for children with leukaemia in the paediatric oncology ward of King Saud Medical City, Saudi Arabia - Aldawsari, Mujibah; Soh, Kim Lam; Abdul Raman, Rosna; Mohd Taib, Niazlin; Aboshaiqah, Ahmad (Penerbit Universiti Sains Malaysia, 2023)
Background: Hands are the most common vehicle of pathogen transmission in a healthcare setting. Therefore, hand hygiene is the leading method of reducing healthcare associated infections. This study aimed to determine the knowledge, attitude and practice (KAP) of hand hygiene and predictors for poor hand hygiene practice among healthcare workers who care for children with leukaemia in the paediatric oncology ward of King Saud Medical City (KSMC) in Saudi Arabia. Methods: One hundred and ninety medical doctors and nurses, who were registered with the Saudi Commission for Health Specialities, were selected to participate in this cross-sectional study using a simple sampling technique. Their KAP of hand hygiene was assessed using a self-structured questionnaire and the collected data was analysed using IBM® SPSS® version 26.0. Results: Of the 190 healthcare workers, 74.7% were nurses and 25.3% were medical doctors. Among the participants, 53.7% (102) had good knowledge of hand hygiene, 51.6% (98) had positive attitudes towards hand hygiene and 55.8% (106) practised satisfactory hand hygiene. Bachelor education level (adjusted OR = 2.736; 95% CI = 1.101, 6.799; P = 0.030), postgraduate education level (adjusted OR = 6.256; 95% CI = 2.171, 18.028; P = 0.001), poor knowledge (adjusted OR =2.575; 95% CI = 1.263, 5.246; P = 0.009) and negative attitude (adjusted OR = 4.702; 95% CI = 1.263, 5.246; P < 0.001) were the significant predictor variables of unsatisfactory hand hygiene practice among healthcare workers. Conclusion: The performance of hand hygiene among healthcare workers is still far less than optimal, particularly in settings like oncology units. Effective programmes are needed to increase their awareness of hand hygiene KAP, while strict guidelines are needed to reduce nosocomial infections.